Pemahaman Konsep Peserta Didik dengan Menggunakan Graded Response Models (GRM) - Tama, Arfani Manda; Rinaldi, Achi; Andriani, Siska (Universitas Islam Negeri Raden Intan Lampung, 2018)
The objective of the study was to analyze the students' comprehension ability concept by using Graded Response Models (GRM). This research is a type of qualitative research with descriptive approach. The subjects of the study were students of class VIII of 6 people by purposive sampling. Technique of collecting data is done by written test (essay) and interview. Data analysis technique is using Graded Response Models (GRM) test, which is then combined with data reduction, data presentation, and conclusion. The results showed that students who have high ability category of 18.19%, 60.6% moderate students, and low-ability students 21.21%. This can be seen from the scores obtained from the students' ability to comprehend the concept of mathematical concepts, and obtained the graph of parameter estimation results by using Graded Response Models can be increased from the lowest ability of learners that is θ (-4) to the highest ability of learners ie θ (4) for each item item category.